2013
DOI: 10.1016/j.jmb.2013.06.039
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Extension of UBE2E Ubiquitin-Conjugating Enzymes Limits Chain Assembly

Abstract: Protein ubiquitylation depends upon the concerted action of ubiquitin-conjugating enzymes (E2s) and ubiquitin ligases (E3s). All E2s have a conserved ubiquitin-conjugating (UBC) domain but many have variable extensions N- and C-terminal to the UBC domain. For many E2s, the function of the extension is not well understood. Here, we show that the N-terminal extension of the UBE2E proteins regulates formation of polyubiquitin chains by the processive UBC domain. Target proteins are therefore monoubiquitylated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 42 publications
5
50
1
Order By: Relevance
“…1b) also replicates the same trend as seen in E3 auto-ubiquitination assays (compare the amount of unmodified substrate left and the poly-ubiquitinated smear). In contrast to the observation of Schumacher et al [28], we found that the deletion of the first 20 residues of Ube2E1 (Ube2E1 ΔN20 ) displayed only a marginal enhancement over the full-length version of the protein (data not shown). We therefore concluded that the entire N-terminal extension, and not a part of it, is responsible for attenuation of the activity of the Ube2E1.…”
Section: N-terminal Extension Restricts Ube2e1 Activitycontrasting
confidence: 99%
See 1 more Smart Citation
“…1b) also replicates the same trend as seen in E3 auto-ubiquitination assays (compare the amount of unmodified substrate left and the poly-ubiquitinated smear). In contrast to the observation of Schumacher et al [28], we found that the deletion of the first 20 residues of Ube2E1 (Ube2E1 ΔN20 ) displayed only a marginal enhancement over the full-length version of the protein (data not shown). We therefore concluded that the entire N-terminal extension, and not a part of it, is responsible for attenuation of the activity of the Ube2E1.…”
Section: N-terminal Extension Restricts Ube2e1 Activitycontrasting
confidence: 99%
“…While studying the E2 preference of the RING E3 ligase RNF4 (RING finger protein 4), we had observed limited activity of Ube2E1 (Datta et al, unpublished data) similar to the observations with the heterodimeric E3 ligase BRCA1-BARD1 [27]. It has also been demonstrated that the N-terminal extensions of Ube2Es limit the chain-building capability of the UBC domain, though the molecular mechanism behind this remained unclear [28]. We probed further into this N-terminal mediated activity reduction and show that not the mere presence but the E3-catalyzed intramolecular auto-ubiquitination (selfubiquitination) of the disordered N-terminal extensions acts as the mechanism restricting activity of Ube2E class of the E2 enzymes.…”
Section: Introductionsupporting
confidence: 56%
“…This may be because a number of different interactions can promote the formation of polyubiquitin chains. For example, non-covalent interaction between ubiquitin and the backside of some E2s enhances chain formation (47), and polyubiquitylation of cIAP2 is reduced when this interaction is disrupted (48). It is therefore possible that once cIAP1 is monoubiquitylated, the ubiquitin moiety attached to cIAP1 could recruit E2ϳUb by binding to the backside of the E2.…”
Section: Discussionmentioning
confidence: 99%
“…The flexible extensions that turn outward from the UBC core domain are essential for some E2s, where they direct subcellular localization 108 , stabilize the E1 interaction, act on substrate selectivity 108 , and regulate the Ub chain assembly 109 . As mentioned earlier, the presence of these extensions determine the classification of the E2 enzymes.…”
Section: E2s Are Regulated By the Flexible Extensions That Are Apart mentioning
confidence: 99%
“…The N-terminal extension in UBE2E1 (UbcH6 -class III E2, Table 3) inhibits the polyubiquitin chain assembly, as shown by two independent studies but with distinct mechanisms. The initial studies show that the UBE2E1 N-terminal extension regulates the Ub chain assembly on its E3 ligases 109 , and that the N-terminal extensions are intrinsically disordered regions, thereby auto-inhibiting the Ub chain assembly formation on the cIAP2 E3 ligase 109 . On the contrary, more recent findings using mutational analysis on UBE2E1 reveal that the reduction of ubiquitinationmediated activity towards E3/substrate is likely due to auto-ubiquitination (selfubiquitination) on the Lys residues in the N-terminal extension 110 .…”
Section: E2s Are Regulated By the Flexible Extensions That Are Apart mentioning
confidence: 99%